The Ameliorating Effects of n-3 Polyunsaturated Fatty Acids on Liver Steatosis Induced by a High-Fat Methionine Choline-Deficient Diet in Mice - Šmíd, Václav; Dvořák, Karel; Stehnová, Kamila; Strnad, Hynek; Rubert, Josep; Stříteský, Jan; Staňková, Barbora; Stránská, Milena; Hajšlová, Jana; Brůha, Radan; Vítek, Libor (International journal of molecular sciences, 2023)
The pathogenesis of non-alcoholic fatty liver disease (NAFLD) is associated with abnormalities of liver lipid metabolism. On the contrary, a diet enriched with n-3 polyunsaturated fatty acids (n-3-PUFAs) has been reported to ameliorate the progression of NAFLD. The aim of our study was to investigate the impact of dietary n-3-PUFA enrichment on the development of NAFLD and liver lipidome. Mice were fed for 6 weeks either a high-fat methionine choline-deficient diet (MCD) or standard chow with or without n-3-PUFAs. Liver histology, serum biochemistry, detailed plasma and liver lipidomic analyses, and genome-wide transcriptome analysis were performed. Mice fed an MCD developed histopathological changes characteristic of NAFLD, and these changes were ameliorated with n-3-PUFAs. Simultaneously, n-3-PUFAs decreased serum triacylglycerol and cholesterol concentrations as well as ALT and AST activities. N-3-PUFAs decreased serum concentrations of saturated and monounsaturated free fatty acids (FAs), while increasing serum concentrations of long-chain PUFAs. Furthermore, in the liver, the MCD significantly increased the hepatic triacylglycerol content, while the administration of n-3-PUFAs eliminated this effect. Administration of n-3-PUFAs led to significant beneficial differences in gene expression within biosynthetic pathways of cholesterol, FAs, and pro-inflammatory cytokines (IL-1 and TNF-α). To conclude, n-3-PUFA supplementation appears to represent a promising nutraceutical approach for the restoration of abnormalities in liver lipid metabolism and the prevention and treatment of NAFLD.
Keywords: játra; Cholesterol; Triglycerides; kyseliny mastné neesterifikované; Racemethionine; Fatty Acids, Unsaturated; Racemethionin; nenasycené mastné kyseliny; Non-alcoholic Fatty Liver Disease; cholesterol; Choline; Diet, High-Fat; n-3 fatty acids; lipidome; Fatty Acids, Omega-3; zvířata; omega-3 mastné kyseliny; myši; cholin; myši inbrední C57BL; Mice; lipids; triglyceridy; Liver; nealkoholová steatóza jater; Mice, Inbred C57BL; Fatty Acids, Nonesterified; non-alcoholic steatohepatitis; dieta s vysokým obsahem tuků; methionin; Methionine; Animals; non-alcoholic fatty liver disease